CORPUS-BASED COMPARATIVE ANALYSIS OF AI TERMINOLOGY IN ENGLISH AND UZBEK - Nazarova Sevinchoy Umarbekovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  The  fast  pace  of  the  Artificial  Intelligence  (AI)  development  has resulted in the appearance of an extremely large amount of specialized vocabulary, most of which is in English. The paper is a corpus-based comparative analysis of AI terminology  in  English  and  Uzbek  that  analyzes  the  usage  patterns,  translation strategies, and semantic adaptation. The study based on two similar corpora that are compiled  using  scholarly  articles,  news  outlets,  and  online  editions,  finds  main distinctions between frequency, lexical organization, and conceptual equivalence. The results  show  that  English  AI  terms  have  a  high  standardization  and  frequency consistency, whereas Uzbek show a hybrid model of direct translation, transliteration, and borrowing. The paper mentions the difficulties of standardization of terminology and offers suggestions in the further linguistic and pedagogical evolution of Uzbek AI discourse.